2019
DOI: 10.3390/f10111023
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Changes of Soil Organic Carbon Stocks in the Forest Area of Northeastern China

Abstract: Forest soil organic carbon (SOC) accounts for a large portion of global soil carbon stocks. Accurately mapping forest SOC stocks is a necessity for quantifying forest carbon cycling and forest soil sustainable management. In this study, we used a boosted regression trees (BRT) model to predict the spatial distribution of SOC stocks during two time periods (1990 and 2015) and calculated their spatiotemporal changes during 25 years in Liaoning Province, China. A total of 367 (1990) and 539 (2015) sampling sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In forest ecosystems, the combination of remotely-sensed data and BRT model provided a better prediction (Table 3) of SOC and STN stocks in topsoil, which was consistent with previous findings [21,46]. For instance, Chen et al [48] used remote sensing images to predict the topsoil SOC content of a 115-hectare land in crisp County, Georgia.…”
Section: Role Of Remotely-sensed Enviroment Variables In Predicting Tsupporting
confidence: 86%
See 2 more Smart Citations
“…In forest ecosystems, the combination of remotely-sensed data and BRT model provided a better prediction (Table 3) of SOC and STN stocks in topsoil, which was consistent with previous findings [21,46]. For instance, Chen et al [48] used remote sensing images to predict the topsoil SOC content of a 115-hectare land in crisp County, Georgia.…”
Section: Role Of Remotely-sensed Enviroment Variables In Predicting Tsupporting
confidence: 86%
“…In this study, we used the "gbm" software package developed by Elith et al [45] to build the model in the R language environment. The fitting of BRT model was controlled by four parameters: Learning rate (LR), tree complexity (TC), bag fraction (BF), and tree number (NT) [46]. LR represents the contribution of each tree in the model to the final fit model.…”
Section: Boosted Regression Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Were et al [42] used the RF model to predict the SOC stocks and concluded that the RF model could explain 52% of the spatial changes of SOC in an Afromontane landscape. In Liaoning Province of China, Wang et al [43] used a BRT model and nine environmental variables to predict the spatial distribution of SOC stocks of topsoil forests and could explain 58% of the spatial change of SOC stocks.…”
Section: Uncertainty In Current Researchmentioning
confidence: 99%
“…Data-driven empirical models were also applied to simulate SOC across temporal scales by developing the predictive relationships between SOC and spatially varying environmental covariates including topographic, climatic, vegetative, geographic and pedological factors [19,20]. The basis of data-driven empirical models in simulating SOC temporal dynamics is the space-for-time substitution (SFTS) assumption [14,21,22], i.e., the data-driven empirical models being established between SOC measurements and spatially varying environmental covariates at current periods could be extrapolated to future SOC estimation by substituting the current covariates with that of future periods.…”
Section: Introductionmentioning
confidence: 99%